Association of uric acid levels with components of metabolic syndrome and non-alcoholic fatty liver disease in overweight or obese children and adolescents - Anajás S. Cardoso; Nathalia C. Gonzaga; Carla C.M. Medeiros; Danielle F. de Carvalho (Brazilian Society of Pediatrics, 2013)
Objective: To investigate the association between serum uric acid concentration according to the presence or absence of non-alcoholic fatty liver disease (NAFLD) and/or metabolic syndrome (MS) in overweight or obese children and adolescents. Methods: This was a cross-sectional study conducted from April of 2009 to March of 2010, including 129 children and adolescents treated at the Center for Childhood Obesity. Anthropometric data, blood pressure measurements, and laboratory test results were obtained, and NAFLD diagnosis was made by ultrasound. The diagnosis of MS was made using the criteria of the National Cholesterol Education Program/Adult Treatment Panel III, adapted to age range. The chi-squared test or or Fisher's test were used to evaluate the association of uric acid with the groups, with a 95% confidence interval. One- way analysis of variance (ANOVA) was used for comparison of means. Multiple logistic regression was used for adjustment of variables. The data were analyzed with the Statistical Package for Social Sciences (SPSS), release 17. Results: High levels of uric acid were significantly associated with adolescence, MS, and systolic blood pressure. The highest quartile of uric acid showed significantly higher values of body mass index, waist circumference, systolic blood pressure, diastolic blood pressure, triglycerides, total cholesterol, and homeostatic model assessment index (HOMA-IR), and lower mean values of HDL cholesterol. In the final model, only age range and the presence of MS remained associated with uric acid levels. Conclusions: High levels of uric acid were associated with MS and adolescence, which was not observed with NAFLD.